The Impact of Corporate Image on Consumer Engagement in Sustainable Consumption - Makūnaitė, Greta; Kiaušienė, Ilona (Vilnius University Proceedings, 2023)
In order to raise public awareness of sustainability, companies need to take an important step towards sustainable consumption. A positive corporate image can help consumers to change their consumption habits and promote sustainable consumption. Corporate social responsibility becomes important in the context of corporate image, showing how companies themselves contribute to solving social, economic and environmental problems. Corporate image – what consumers think of a company – can influence consumer engagement in sustainable consumption. The objective is to determine the impact of corporate image on consumer engagement in sustainable consumption. The results showed that a positive corporate image can lead to consumer satisfaction and long-term customer retention, i.e. loyalty, indicating a positive consumer engagement with sustainable consumption. Consumer engagement in sustainable consumption is not only determined by a positive corporate image together with CSR, but also by the external and internal environment of consumers